¿Lengua de inmigración o lengua extranjera? Enseñanza del putonghua en una escuela pública de la Ciudad de Buenos Aires - Sartori, María Florencia (Pontificia Universidad Católica del Perú, 2023)
This paper analyzes, from a glotopolitical perspective, the establishment and functioning of a Spanish-Putonghua bilingual public school in the city of Buenos Aires. This institution and its implementation demonstrate a concern for the educational inclusion of Chinese migrants and their descendants, as well as for the preservation and learning of the immigration language. Throughout this article, we will show how Putonghua is constructed both as a language of instruction and as an “object language” in legal regulations, classes, and in the speeches of officials. We argue that the motivation underlying the creation of this school is the increasing importance that Putonghua has gained globally in recent years.

Este trabajo analiza, desde una perspectiva glotopolítica, la conformación y el funcionamiento de una escuela pública bilingüe español-putonghua de la ciudad de Buenos Aires, Argentina. Esta institución y su puesta en funcionamiento evidencian una preocupación por la inclusión educativa de los migrantes chinos y sus descendientes, a la vez que por el mantenimiento y aprendizaje de la lengua de inmigración. A lo largo de este artículo, se mostrará cómo el putonghua se construye como lengua de instrucción, y, al mismo tiempo, como “lengua objeto”, en la normativa legal, las clases y en los discursos de los funcionarios. Sostenemos que la motivación que subyace a la creación de esta escuela es la importancia que el putonghua fue ganando mundialmente en los últimos años.
Immigration Language or Foreign Language? Teaching Putonghua in a Public School in Buenos Aires
Keywords: Chinese immigration; Putonghua; Teaching; Buenos Aires; Argentina; Migración china; Putonghua; Enseñanza; Buenos Aires; Argentina; https://purl.org/pe-repo/ocde/ford#6.02.06